2008
DOI: 10.1310/tsr1506-542
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technology for Treating Individuals with Aphasia and Concomitant Cognitive Deficits

Abstract: Purpose-This article describes three individuals with aphasia and concomitant cognitive deficits who used state-of-the-art computer software for training conversational scripts.Method-Participants were assessed before and after 9 weeks of a computer script training program. For each participant, three individualized scripts were developed, recorded on the software, and practiced sequentially at home. Weekly meetings with the speech-language pathologist occurred to monitor practice and assess progress. Baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…19 A group were attributed not only to improved language skills but also to improved confi dence and selfesteem. These fi ndings are consistent with results from other studies done by my colleagues and I 10,11 in which improved confi dence and self-esteem were reported by individuals utilizing a computerbased script-training procedure. Although these results are promising, further investigation into computer delivery of specifi c types of aphasia language treatment is warranted.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…19 A group were attributed not only to improved language skills but also to improved confi dence and selfesteem. These fi ndings are consistent with results from other studies done by my colleagues and I 10,11 in which improved confi dence and self-esteem were reported by individuals utilizing a computerbased script-training procedure. Although these results are promising, further investigation into computer delivery of specifi c types of aphasia language treatment is warranted.…”
supporting
confidence: 92%
“…[2][3][4] Several studies have already established that people with aphasia are able to use computers independently with minimal therapist intervention and with demonstrable benefits. [5][6][7][8][9][10][11] Studies designed to assess the feasibility and effi cacy of COT are now emerging. 7,10-12 For example, 7 participants with aphasia of at least 2 years' duration used home computer software designed to improve word retrieval skills.…”
mentioning
confidence: 99%
“… * Included the participants with nonfluent aphasia in Cherney (2008), Cherney & Halper (2008), and Manheim (2009) ** Included the 3 participants from Cherney (2008), and 20 participants from Manheim (2009), AAT=Aachen Aphasia Test; ANELT=Amsterdam-Nijmegen Everyday Language Test; AOS=Apraxia of speech; AQ=Aphasia Quotient; BOSS=Burden of Stroke Scale; CADL-2=Communication Activities of Daily Living; CAL=Communicative Activity Log; CETI=Communicative Effectiveness Index; QCL=Quality of Communication Life Scale; SAQOL=Stroke and Aphasia Quality of Life Scale; WAB=Western Aphasia Battery …”
Section: Figurementioning
confidence: 99%
“…Table 1 provides a summary of 13 publications that provide evidence for this approach (Bilda, 2011; Cherney & Halper, 2008; Cherney, Halper, Holland, & Cole, 2008; Cherney, Halper, & Kaye, 2011; Cherney, Kaye & Van Vuuren, 2014; Cherney, Kaye, Lee, & Van Vuuren, 2015; Goldberg, Haley, & Jacks, 2012; Lee, Kaye, & Cherney, 2009; Manheim, Halper, & Cherney, 2009; Nobis-Bosch, Springer, Radermacher, & Huber, 2011; Van Vuuren & Cherney, 2014; Youmans, Holland, Munoz, & Bourgeois, 2005; Youmans et al, 2011). It is important to note that several of the publications present different analyses of data from the same set of subjects (e.g., Cherney et al, 2014, 2015; Van Vuuren & Cherney, 2014); however, overall, the studies were conducted by five different research groups and include over 60 unique participants.…”
mentioning
confidence: 99%
“…The studies on discourse intervention that we found comprised three distinct approaches to the improvement of discourse (in some studies, more than one approach is used). One approach targets word and sentence production (simple and complex clauses) within discourse [56,[70][71][72][73][74]; another involves massed practice of whole discourses, using AphasiaScripts [75][76][77] and a third focuses on supporting participants to improve their discourse macrostructure using story grammar [56,64,68,78]. Overall, the findings from these studies were positive, with clients' improving in language use, the amount and quality of information conveyed, and how the information was structured, although it was not the case that all three elements improved in every case.…”
Section: Discourse Therapy For Adults With Aphasiamentioning
confidence: 99%